Physical characteristics of oily spraying liquids and droplets formed on coffee leaves and glass surfaces - Decaro, Sergio T.; Ferreira, Marcelo Da C.; Lasmar, Olinto (Associação Brasileira de Engenharia Agrícola, 2015)
The physical characteristics of a spray liquid are important in getting a good droplet formation and control efficiency over a particular target. As a function of these characteristics, it is possible to decipher which is the best adjuvant based on the respective concentration used during the spray. Therefore, ten spraying liquids were prepared, which varied in concentrations of pesticide lufenuron + profenofos, mineral oil, water and manganese sulfate. Pendant droplets formed from these mixtures were measured to examine their impact on surface tension. Droplets were applied to the surface of coffee leaves and the surface tension, contact angle formed and the leaf area wetted by the droplet, were measured. A smooth glass surface was taken as a comparative to the coffee leaves. The highest concentrations of oil resulted in lower surface tension, smaller contact angles of droplets on leaf surfaces and larger areas wetted by the droplets. Both surfaces showed hydrophilic behavior.

As características físicas da calda de pulverização são importantes para que haja boa formação de gotas e eficiência de controle sobre determinado alvo. Em função dessas características, pode-se decidir sobre qual o melhor adjuvante, em sua respectiva concentração, poderá ser utilizado durante a pulverização. Para tanto, foram preparadas dez caldas fitossanitárias em que variaram as concentrações do inseticida lufenuron + profenofós, óleo mineral, água e sulfato de manganês. Gotas pendentes formadas a partir dessas misturas foram medidas em sua tensão superficial. Aplicaram-se gotas sobre a superfície de folhas de café e foram medidos a tensão superficial, o ângulo de contato formado e a área da folha molhada pela gota. Uma superfície lisa de vidro foi tomada como comparativo às folhas de café. As maiores concentrações de óleo resultaram em menores valores de tensão superficial, menores ângulos de contato de gotas com a superfície foliar e maiores áreas molhadas pelas gotas. Ambas as superfícies mostraram-se hidrofílicas.
Características físicas de caldas oleosas e de gotas formadas em superfície de folhas de café e de vidro
Keywords: surface tension; contact angle; wetted area; oil; tensão superficial; ângulo de contato; área molhada; óleo